Energy management of community microgrids considering degradation cost of battery. (April 2019) - Hossain, Md Alamgir; Pota, Hemanshu Roy; Squartini, Stefano; Zaman, Forhad; Muttaqi, Kashem M.
Highlights: This paper develops a new formulation to reflect the true operational cost of a microgrid. A dynamic penalty function is integrated into the cost function to optimally charge the battery. Mathematical models are presented to facilitate the analysis. A PSO for evaluating the cost function is designed to find the optimal battery energy management. Abstract: A storage system is a key component of a microgrid. Over the last few years, research has been undertaken to determine optimal management of microgrid resources. Battery storage has a significant impact on the total operational cost as the lifetime of the battery reduces during charging and discharging cycles. In this paper, we propose optimal energy management of a community microgrid in which the cost function includes the degradation cost of the battery and a dynamic penalty to reflect the true operational cost. Particle swarm optimisation (PSO) is used to determine the battery control actions for real-time energy management. Several case studies are presented to demonstrate the effectiveness of the proposed framework in which the new cost function reduces electricity cost by up to 44.50% compared to a baseline method and 37.16% compared to another existing approach.